Personal Branding Strategy in LinkedIn Profile Summary: A Rhetorical Move Analysis - Asyipa Nursani; Tofan Dwi Hardjanto (k@ta: A Biannual Publication on the Study of Languange and Literature, 2024)
Today, LinkedIn is a business-focused social media platform widely preferred for professional networking. The discourse produced in a LinkedIn profile summary can significantly enhance one's personal branding. This study examines the personal branding strategies embedded in the move structure of LinkedIn profile summaries. A genre analysis approach elaborated with the components of personal branding, provides insights into the creation of an effective profile summary. The results of this study show that the self-strength component is a mandatory element in a profile summary. Strengths can be highlighted by presenting experience, skills, educational background, and position. Additionally, there are optional components that can further enhance personal branding, such as presenting achievements, goals, and unique qualities. These findings serve as a reference for LinkedIn users in developing a stronger personal brand through the creation of an effective and efficient profile summary.